Eleven-Month-Olds Link Sound Properties With Animal Categories - Vukatana, Ena; Zepeda, Michelle S.; Anderson, Nina; Curtin, Suzanne; Graham, Susan A. (Frontiers in Psychology, 2020)
We examined 11-month-olds’ tendency to generalize properties to category members, an ability that may contribute to the inductive reasoning abilities observed in later developmental periods. Across 3 experiments, we tested 11-month-olds’ (N= 113) generalization of properties within the cat and dog categories. In each experiment, infants were familiarized to animal-sound pairings (i.e., dog-barking; cat-meowing), and tested on this association and the generalization of the sound property to new members of the familiarized categories. After familiarization with a single exemplar, 11-month-olds generalized the sound to new category members that were both highly similar and less similar to the familiarized animal (Expt. 1). When familiarized with mismatched animal-sound pairings (Expt. 2; i.e., dog-meowing; cat-barking), 11-month-olds did not learn or generalize the sound properties, suggesting that infants have pre-existing expectations about the links between the characteristic sound properties and the animal categories. When familiarized with unfamiliar sound-animal pairings (Expt. 3; i.e., dog-unfamiliar sound), 11-month-olds linked the animals with the novel sounds but did not generalize to new category members. Taken together, these findings highlight the conditions under which young infants generalize properties from one exemplar to other category members.